Use of Favipiravir for the Treatment of Coronavirus Disease 2019 in the Setting of Hospitel - Bhitta Surapat (2022)
Objective: In a setting with a limited capacity for hospitalization, "hospitels" have been developed by using hotels as extension healthcare facilities for patients with mild illness. This study examined the clinical evidence of patients with coronavirus disease 2019 (COVID-19) who were treated with favipiravir, the main medication for treating COVID-19, in the hospitel setting in Thailand. Methods: We retrospectively collected demographic and clinical information, medication treatment, and outcome data for all patients who received favipiravir for COVID-19 during admission to a hospitel from April 27, 2021, to July 2, 2021. Risk factors for adults who could not complete treatment in a hospitel and who required hospitel transfer were analyzed. Results: In total, 421 patients were included in the study. Most patients (94.5%) received favipiravir to treat COVID-19 pneumonia. Adjunctive corticosteroids were prescribed to 42.3% of patients. Concerning the treatment outcome, 83.6% of patients completed treatment at a hospitel, and only two deaths occurred. No serious adverse drug reactions were observed. On multivariate analysis, age (odds ratio (OR) = 1.06; 95% confidence interval (CI) = 1.02-1.10, P=0.002), dyspnea (OR = 2.84; 95% CI = 1.25-6.44, P=0.013), loss of taste (OR = 107.63; 95% CI = 1.24-9337.39, P=0.040), corticosteroid use (OR = 12.56; 95% CI = 3.65-43.18, P < 0.001), and an extended duration of favipiravir use (OR = 16.91; 95% CI = 7.29-39.24, P < 0.001) were associated with a higher risk of hospitel transfer. Conclusions: Low rates of hospitel transfer and mortality were observed in mild-to-moderate COVID-19 patients treated with favipiravir at hospitel. Caution might be required in elderly patients, patients with dyspnea or a loss of taste, and patients receiving a 10-day course of favipiravir or adjunctive corticosteroids because these patients might require further management in the hospitel.